Bioefficacy of an oil-emulsion formulation of entomopathogenic fungus, Metarhizium anisopliae against adult red palm weevil, Rhynchophorus ferrugineus - Lei, Cheong Jia; Raja Ahmad, Raja Hasya Ilyana; Abdul Halim, Najihah; Asib, Norhayu; Zakaria, Azlina; Azmi, Wahizatul Afzan (Multidisciplinary Digital Publishing Institute, 2023)
The red palm weevil (RPW), Rhynchophorus ferrugineus, poses a severe threat to agro-industrial crops, particularly major cultivated palm species. Infestations result in economic losses due to reduced fruit quality and yield. The entomopathogenic fungus, Metarhizium anisopliae, has shown promise as a potential biocontrol agent against the RPW. However, the use of an emulsion formulation of M. anisopliae for managing this serious insect pest has yet to be fully explored. The oil-emulsion formulation containing this entomopathogen may enhance the conidia’s stability, prolong its lifetime, and reduce the impact of heat stress or UV irradiation on the fungus. Therefore, this study aimed to investigate the bioefficacy of a new oil-in-glycerol emulsion formulation on mycoinsecticidal activity against RPW adults by direct and indirect bioassays. Results showed that conidia concentration was directly proportional to the RPW mortality percentage. The LT50 of 8.183 days was achieved by the conidial formulation against RPW, with a significantly lower LC50 (1.910 × 105 conidia mL−1) compared to the aqueous conidia suspension (LT50 = 8.716 days; LC50 = 7.671 × 105 conidia mL−1). Indirect bioassays revealed that the oil-in-glycerol emulsion had a disease-spreading ability that resulted in up to 56.67% RPW mortality. A zero E-value reading indicates that the DNA sequence being studied is highly similar to that of the fungal species M. anisopliae, which has been identified in the NCBI database. Although the new emulsion formulation has improved the efficacy and pathogenicity of M. anisopliae in vitro, it is important to also consider the fungal pathogen’s compatibility with other agricultural practices to prevent any loss of control efficiency in the actual usage environment.